2002
DOI: 10.1055/s-2002-33210
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Thrombosis after Variceal Endoscopic Sclerotherapy in Cirrhotic Patients: Role of Genetic Thrombophilia

Abstract: Endoscopic sclerotherapy of esophageal varices may represent a trigger factor for portal vein thrombosis in cirrhotic patients with genetic thrombophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 15 publications
2
72
2
1
Order By: Relevance
“…PVT has been described following endoscopic sclerotherapy in patients with cirrhosis in association with these thrombophilic conditions. 65 Endotoxemia in cirrhosis may increase the risk of PVT in cirrhosis.…”
Section: Vascular Endothelial Injurymentioning
confidence: 99%
“…PVT has been described following endoscopic sclerotherapy in patients with cirrhosis in association with these thrombophilic conditions. 65 Endotoxemia in cirrhosis may increase the risk of PVT in cirrhosis.…”
Section: Vascular Endothelial Injurymentioning
confidence: 99%
“…Splenomegaly and a large splenic vein diameter are independent risk factors for PVT after splenectomy in patients with concomitant cirrhosis and portal hypertension [39,46,47] . The role of sclerotherapy as a potential trigger for PVT is controversial [48,49] . Some recent reports showed that thrombopoietin receptor agonists might be associated with an increased incidence of PVT in patients with cirrhosis [50,51] .…”
Section: Etiology Of Pvt In Cirrhosismentioning
confidence: 99%
“…35,36 The role of sclerotherapy and cyanoacrylate glue injection as a potential trigger factor for PVT is controversial but has been reported in literature. [37][38][39] Such associations could be as a result of selection bias of patients with more severe portal hypertension.…”
Section: Pathophysiologymentioning
confidence: 99%